Acne Vulgaris with Polycystic Ovarian Syndrome: A Case Report - Sikder, Romana; Khan, Morshed Uddin; Salam, Shaikh Salman; Islam, Sunjida (Eastern Medical College Journal, 2024)
Acne vulgaris is a common chronic skin condition of pilosebaceous units that can be presented with non-inflammatory lesions, inflammatory lesions or mixture of both. This affects a large portion of teenagers and young adults (aged 15-40 years). About 85% of adolescents experience it. It is a polymorphic disorder (comedons, papules, pustules, nodules, cysts and sometimes scarring). Besides, Polycystic Ovarian Syndrome (PCOS) is a heterogeneous disorder of hormonal imbalance that occurs when ovaries produce unusual hormones during reproductive age. Clinically it is manifested by acne, oligomenorrhoea, subfertility and hirsutism. The presence of hyper-androgenism and metabolic problems may lead to the development of this condition. In this case study, a female aged 22 years presented with papules, pustules, some nodules in face and irregular menstrual cycle with no history of receiving any hormonal treatment. Clinical data including age, weight, height, BMI, menstrual history and androgenic sign (hirsutism, alopecia, acanthosis nigricans) were recorded with hormonal assay. A pelvic ultrasonogram was also done. Eastern Med Coll J. July 2024; 9 (2): 125-128